Rencana Bisnis Fitur Monitoring Real-Time Coaching dengan Suara pada Smartband (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
The government's "social distancing" and "work from home" policies are carried out to reduce the risk of transmitting the virus between humans, which has the potential to decrease physical activity and exercise habits. In fact, regular exercise can play a role in increasing the body's immune system so that it can indirectly increase the body's defense against Covid-19. If sports activities are connected with technology, they will find many combinations and bring up various fresh ideas in sports. Smartband is a type of wearable that functions as a fitness tracker or health tracker for those who want to increase their fitness level. To improve the features on the smartband, use a Design thinking approach that focuses on humanity by integrating human needs, technological capabilities, and business success. The Business Model Canvas can illustrate the rationale for how to create existing value. Business Strategy requires Operational Analysis, Marketing Analysis, Financial Analysis and Risk Analysis